The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/es303401b
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Trends in Lake Erie Hypoxia, 1987–2007

Abstract: Hypoxic conditions, defined as dissolved oxygen (DO) concentrations below 2 mg/L, are a regular summertime occurrence in Lake Erie, but the spatial extent has been poorly understood due to sparse sampling. We use geostatistical kriging and conditional realizations to provide quantitative estimates of the extent of hypoxia in the central basin of Lake Erie for August and September of 1987 to 2007, along with their associated uncertainties. The applied geostatistical approach combines the limited in situ DO meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(140 citation statements)
references
References 35 publications
(61 reference statements)
9
129
2
Order By: Relevance
“…On the other hand, the DO concentration never fell below 2 mg/L in Qiandaohu Lake, China, where the DO depth profiles were closely linked to the water temperature depth profiles [19]. The decrease of DO with depth is commonly observed in reservoirs as photosynthesis increases oxygen level in the surface water while respiration of bacteria decomposing dead organic matter consumes all the dissolved oxygen in the bottom water column coupled with insufficient exchange with oxygenated surface water [30]. However, a slight increase of DO content was observed at the water column of the Bakun Reservoir between 12 m and 20 m which is most likely due to the additional water discharged from the spillway where the water intake was at a depth of approximately 15 m. The rapid water movement due to the additional water withdrawal at the particular water column promotes the mixing of the low DO water with a large volume of oxygenated colder water inflow from tributaries around the reservoir [14].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the DO concentration never fell below 2 mg/L in Qiandaohu Lake, China, where the DO depth profiles were closely linked to the water temperature depth profiles [19]. The decrease of DO with depth is commonly observed in reservoirs as photosynthesis increases oxygen level in the surface water while respiration of bacteria decomposing dead organic matter consumes all the dissolved oxygen in the bottom water column coupled with insufficient exchange with oxygenated surface water [30]. However, a slight increase of DO content was observed at the water column of the Bakun Reservoir between 12 m and 20 m which is most likely due to the additional water discharged from the spillway where the water intake was at a depth of approximately 15 m. The rapid water movement due to the additional water withdrawal at the particular water column promotes the mixing of the low DO water with a large volume of oxygenated colder water inflow from tributaries around the reservoir [14].…”
Section: Discussionmentioning
confidence: 99%
“…The invasive Dreissenid mussels have caused measurable drops in calcium and alkalinity due to shell burial in Lakes Erie and Michigan (Barbiero et al, 2012). A complex interplay of climate change, agricultural practices, and invasive species is thought to be responsible for the re-eutrophication of Lake Erie and associated increases in the extent of hypoxia (e.g., Kane et al, 2014;Zhou et al, 2013). Large shifts in food webs have occurred concomitantly, including increasing occurrences of harmful algal blooms , large changes in zooplankton abundance and composition (Barbiero et al, 2009), and major changes in the relative abundance of commercially important fish species (e.g., Bunnell et al, 2009;Pothoven et al, 2001;Claramunt et al, 2007).…”
Section: Regional Settingmentioning
confidence: 99%
“…Most aquatic organisms are only able to tolerate environments with sufficient dissolved oxygen levels including most fish species, which are unable to tolerate DO < 4 mg/L [2]. The occurrence of hypoxia in Lake Erie, particularly in the central basin, have been observed and studied in Lake Erie since 1929 [3], but the recent increases in hypoxia incidents have led to renewed interest in the phenomenon [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…The predominant hypothesis is that cultural eutrophication promoted increased algal production resulting in higher biological oxygen demand [3]. Other studies found that there is a close relationship between biological production and hypolimnetic oxygen depletion rates and that those rates, corrected for vertical-mixing and other physical factors, have been increasing overall since 1929 [4,11]. The hypothesized connection between cultural eutrophication and hypolimnetic oxygen depletion led to the Great Lakes Water Quality Agreement between the U.S. and Canada that stipulated a limit on nutrient loading (11,000 metric tons annually) into the Great Lakes [12].…”
Section: Introductionmentioning
confidence: 99%